Investment Pattern of Financially Literate Persons in Nepal (The International Research Journal of Management Science, 2017)
The paper investigates the investment pattern of financially literate persons based on 314 individual investors of Nepal. The mean, ANOVA and logistic regression is used. The results show that investors have higher level of financial literacy level. Among them, male participants, investors of age group 20-30 and income level of Rs 50,001 and above scored higher in financial literacy. The financial literacy increased with increase in the education level as well as the income level. The study reveals that there are differences between investment patterns among the high and low financially literate persons. These groups differ in term of their investment preferences, investment objectives, investment tenure, sources of investment advices and awareness level.